Soil and agronomic factors influencing fodder production in the semi-arid and arid zones of West Africa. Part I. In the semi-arid zone of Mali. Part II. In the arid zone of Niger - Ahmad, N. (International Livestock Centre for Africa, 1986)
Examines the environment including climate, soils & vegetation of Mali & Niger; maintainance of soil productivity; research on crop/forage production in progress at ILCA, ICRISAT, INRAN and CILSS; and research needs. Includes suggestions for the modification of the ILCA program in Mali and to carry out the proposed new studies, and implications for centre facilities.